2013
DOI: 10.1007/s13539-013-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of muscle quality: N‐terminal propeptide of type III procollagen and C‐terminal agrin fragment responses to resistance exercise training in older adults

Abstract: BackgroundN-terminal peptide of procollagen type III (P3NP) and C-terminal agrin fragment (CAF) are circulating biomarkers that are related to lean body mass in older adults. P3NP is a circulating marker reflective of muscular structural remodeling while CAF is a circulating marker of neuromuscular remodeling. As resistance exercise is an established intervention that can effectively improve muscle quality, we sought to evaluate circulating biomarker changes corresponding to a resistance exercise intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 39 publications
3
110
0
3
Order By: Relevance
“…We found that circulating CAF increased to a clinically meaningful magnitude while changes in circulating P3NP were less clear, but appeared to reflect muscle hypertrophy [177]. While assessment of P3NP and CAF from blood samples may provide minimally invasive and clinically informative measures of skeletal muscle status in older adults, further research is needed to elucidate whether P3NP, CAF, or other biomarkers can reflect muscle qualitative adaptations with larger and longer studies.…”
Section: Circulating Biomarkersmentioning
confidence: 77%
See 1 more Smart Citation
“…We found that circulating CAF increased to a clinically meaningful magnitude while changes in circulating P3NP were less clear, but appeared to reflect muscle hypertrophy [177]. While assessment of P3NP and CAF from blood samples may provide minimally invasive and clinically informative measures of skeletal muscle status in older adults, further research is needed to elucidate whether P3NP, CAF, or other biomarkers can reflect muscle qualitative adaptations with larger and longer studies.…”
Section: Circulating Biomarkersmentioning
confidence: 77%
“…We evaluated changes in circulating concentration of P3NP and CAF in response to a preliminary intervention designed to increase muscle quality but not mass [177]. We found that circulating CAF increased to a clinically meaningful magnitude while changes in circulating P3NP were less clear, but appeared to reflect muscle hypertrophy [177].…”
Section: Circulating Biomarkersmentioning
confidence: 96%
“…94,95 Such factors include for instance leptin, 96 ghrelin, 97 and obestatin 98 which are all thought to play a major role in cancer cachexia. These emerging biomarkers were MMP-generated degradation fragment of collagen 6 (C6M) 68 Type VI collagen N-terminal globular domain epitope (IC6) 68 N-terminal propeptide of type III procollagen (P3NP) 69 C-terminal agrin fragment (CAF) 69 Methyl-d 3 -Methylhistidine (D-3MH) 70 Growth differentiating factor-15 (GDF-15) 71 Follistatin (FST) 72 Irisin 72 Ghrelin 73 Leptin 73 β-Dystroglycan 74 Dystrophin 74 Tartrate-resistant acid phosphatase 5a (TRACP5a) [75][76][77][78] MMP, matrix metalloproteinase. investigated in oncologic patients as diagnostic and/or predictive markers, as well as their impact on patient survival.…”
Section: Current News On Biomarker Researchmentioning
confidence: 99%
“…87 It is released into circulation during collagen synthesis in soft lean tissue, and its levels have been associated with changes in the lean mass of elderly patients. 63,91 Myostatin Although it seems a natural candidate for an atrophy biomarker, as it directly mediates catabolic signaling, the data of a recent study in CC could not confirm the role of circulating myostatin as a biomarker for muscle wasting in humans.…”
Section: P3npmentioning
confidence: 99%